Frequency of rs35803318 single nucleotide polymorphism of ACE2 gene among the Kazakhs - Bisseneva А.К.; Pogossyan, G.P.; Li, K.G.; Bazarbaeva, S.M.; Maratova, A.S.; Evtushenkov, A.N. (Fundamental and Experimental Biology, 2024)
In the article the results of genotyping of DNA samples obtained from the study participants on the single nucleotide polymorphism (SNP) rs35803318 (C/T) of the ACE2 gene were presented. Genotyping was carried out by real-time polymerase chain reaction (PCR) using the technique Amplification of the Refractory Mutation System (ARMS). The frequencies of rs35803318 (C/T) genotypes and alleles in 96 representatives of the Kazakh ethnic group living in the Karaganda region were analyzed. The ACE2 gene (angiotensin-converting enzyme 2) was extensively investigated due to its role in susceptibility to infection by the SARS-CoV-2 virus causing COVID-19. The ACE2 gene encodes a protein that serves as a receptor for the virus, and its variations can affect a person’s susceptibility to infection. The ACE2 protein plays a role in the regulation of angiotensin and the effect on blood pressure. Therefore, there is a link between ACE2 gene polymorphisms, including rs35803318, and the development of cardiovascular diseases. According to the results of our study, the CT genotype (63.5 %) is the most common among Kazakhs, the CC genotype was 20.8 % and the TT genotype was 15.6 %. The distribution of polymorphism alleles is as follows: allele C — 52.6 %, allele A — 47.4 %.